Creepy - Habuka, Yuri 1988- (Eureka, 2017)
"Based on a novel by Yutaka Maekawa, Creepy follows ex-police detective and criminal psychologist Takakura, who moves to a quiet suburban town seeking peace and quiet. When a former colleague asks for his assistance on a case involving a disappearing family his investigation leads him to suspect that his neighbour is a psychopath who comes into peoples households and takes over their lives. With a stunning cast made up of many of Japans leading actors including Hidetoshi Nishijima, Yuko Takeuchi and Teruyuki Kagawa, "Creepy" expertly mixes the genre conventions of the American thriller and Japanese horror to create this breath taking thriller. The Masters of Cinema series is proud to present the films UK home video debut in a dual-format edition. [...]" [amazon.de]
Original: Japan 2016
New 1080p transfer of the film on Blu-ray, with a progressive encode on the DVD; optional English sutitles; a new interview with director Kiyoshi Kurosawa; original theatrical trailer; 24-page booklet featuring a new essay on the film by critic Jasper Sharp and illustrated with stills from the film's production
Bildformat 1.85:1
Keywords: Film; DVD-Video